1994
DOI: 10.1007/bf00014598
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular basis for impairment of photosynthetic potential

Abstract: Ozone induces reductions in net photosynthesis in a large number of plant species. A primary mechanism by which photosynthesis is reduced is through impact on carbon dioxide fixation. Ozone induces loss in Rubisco activity associated with loss in concentration of the protein. Evidence is presented that ozone may induce oxidative modification of Rubisco leading to subsequent proteolysis. In addition, plants exposed to ozone sustain reduction in rbcS, the mRNA for the small subunit of Rubisco. This loss in rbcS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 48 publications
4
48
0
7
Order By: Relevance
“…Among the parameters most associated with this decrease in the present study are maximum rate of carboxylation of rubisco, which presented significant reduction in Fepagro (experiment 1), Guapo (experiment 1) and Pinto (experiment 5), and carboxylation efficiency which presented a significant reduction in Fepagro cultivar (experiment 4) and Guapo cultivar (experiment 1) and the tendencies to reduction in Fepagro cultivar (experiment 1), Macotaço cultivar (experiment 1) and Pinto cultivar (experiment 5). Both maximum rate of carboxylation of rubisco, and carboxylation efficiency reflect the activity of rubisco in vivo (Rogers and Humphries 2000), and carboxylation reductions were considered the main factors responsible for impairment in photosynthesis by Pell et al (1994) and Guidi et al (2001). Guidi et al (2000), working with bean plants of Pinto cultivar, also found results that agree with the idea that the primary target of ozone are the enzymes involved in the Calvin cycle and, particularly, rubisco activity.…”
Section: Dry Mass Accumulationsupporting
confidence: 56%
See 1 more Smart Citation
“…Among the parameters most associated with this decrease in the present study are maximum rate of carboxylation of rubisco, which presented significant reduction in Fepagro (experiment 1), Guapo (experiment 1) and Pinto (experiment 5), and carboxylation efficiency which presented a significant reduction in Fepagro cultivar (experiment 4) and Guapo cultivar (experiment 1) and the tendencies to reduction in Fepagro cultivar (experiment 1), Macotaço cultivar (experiment 1) and Pinto cultivar (experiment 5). Both maximum rate of carboxylation of rubisco, and carboxylation efficiency reflect the activity of rubisco in vivo (Rogers and Humphries 2000), and carboxylation reductions were considered the main factors responsible for impairment in photosynthesis by Pell et al (1994) and Guidi et al (2001). Guidi et al (2000), working with bean plants of Pinto cultivar, also found results that agree with the idea that the primary target of ozone are the enzymes involved in the Calvin cycle and, particularly, rubisco activity.…”
Section: Dry Mass Accumulationsupporting
confidence: 56%
“…According to Pell et al (1994), the photosynthetic process may be affected by the occurrence of damage involving stomatal movements, the collection of light or the biochemical stage of CO 2 fixation. The total photosynthetic capacity of the plant may also be reduced by loss of leaves (accelerated senescence, and/or reduced production), and by the increased respiratory rate to perform functions such as repairing cell constituents, or by the increased production of certain compounds (ATP and reductant compounds) needed for detoxification and defense (Mooney and Winner, 1988).…”
mentioning
confidence: 99%
“…A fotossíntese é um processo sensível à poluição aérea e sua redução tem sido constatada com freqüência em plantas ocorrentes ou introduzidas em locais poluí-dos (Inoue & Reissmann 1994, Pandey & Agrawal 1994, Pfanz et al 1994, Reich et al 1994). Segundo Pell et al (1994), o processo fotossintético pode ser afetado pela ocorrência de danos envolvendo os movimentos estomáticos, a coleta de luz ou a etapa bioquímica de fixação do CO2. Como neste estudo não foram observadas diferenças nas taxas de condutância estomática e de transpiração (tabela 1), acredita-se que a redução da fotossíntese tenha sido causada por outros fatores, envolvendo alterações na coleta de luz ou na quantidade e atividade da ribulose-1,5-bisfosfato carboxilase-oxigenase (RUBIS-CO).…”
Section: Resultsunclassified
“…5), respectively. The reduction in A sat , chlorophyll degradation and lipid peroxidation in turn may lead to accelerated leaf senescence (Fangmeier et al, 1994;Mulholland et al, 1997;Pell et al, 1994), which has been widely reported for many species including wheat as a typical physiological symptom induced by elevated O 3 Finnan et al, 1998;Miller et al, 1999;Pell et al, 1994;Ribas et al, 2005). Among foliar pigments, carotenoids play an important role in photosynthetic reaction centra by both participating the process of energy-transfer and providing a mechanism for plant photoprotection against photooxidation (Davies, 2004).…”
Section: Discussionmentioning
confidence: 99%